2017
DOI: 10.5026/jgeography.126.455
|View full text |Cite
|
Sign up to set email alerts
|

Weathering Rates of Stone-built Heritages

Abstract: It is difficult to estimate weathering rates of rocks based on actual landforms. However, using stone-built architectures, artifacts, and traces of human activity on rock surfaces, weathering rates of rocks under weathering-limited conditions can be obtained easily because stone-built heritages, in general, have a geometrical shape and zero-datum levels. In addition, it is possible to estimate weathering rates of a millennium-scale and changes of rates up to a millennium scale. Many studies on weathering rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…These weathering processes are thought to be restricted by direction dependent (Waragai 2005b;Waragai et al 2006;André et al 2012;Hiki 2012;Hiki and Waragai 2014;Waragai 2016), especially for the temples at Angkor. Regarding cultural stone weathering, previous studies have shown the importance of direction or aspect related to heating-cooling repetitions and moisture changes (Meierding 1993;Paradise 1995Paradise , 2002Williams and Robinson 2000;Waragai 2017). Recently, a relationship between the weathering of sandstone pillars and the pillar water content in conjunction with the microclimatic conditions has been pointed out (Hiki and Waragai 2014).…”
Section: Cultural Stone Weathering Researchmentioning
confidence: 99%
“…These weathering processes are thought to be restricted by direction dependent (Waragai 2005b;Waragai et al 2006;André et al 2012;Hiki 2012;Hiki and Waragai 2014;Waragai 2016), especially for the temples at Angkor. Regarding cultural stone weathering, previous studies have shown the importance of direction or aspect related to heating-cooling repetitions and moisture changes (Meierding 1993;Paradise 1995Paradise , 2002Williams and Robinson 2000;Waragai 2017). Recently, a relationship between the weathering of sandstone pillars and the pillar water content in conjunction with the microclimatic conditions has been pointed out (Hiki and Waragai 2014).…”
Section: Cultural Stone Weathering Researchmentioning
confidence: 99%